2013
DOI: 10.1073/pnas.1300585110
|View full text |Cite
|
Sign up to set email alerts
|

DTF1 is a core component of RNA-directed DNA methylation and may assist in the recruitment of Pol IV

Abstract: DNA methylation is an important epigenetic mark in many eukaryotic organisms. De novo DNA methylation in plants can be achieved by the RNA-directed DNA methylation (RdDM) pathway, where the plant-specific DNA-dependent RNA polymerase IV (Pol IV) transcribes target sequences to initiate 24-nt siRNA production and action. The putative DNA binding protein DTF1/SHH1 of Arabidopsis has been shown to associate with Pol IV and is required for 24-nt siRNA accumulation and transcriptional silencing at several RdDM targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
179
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 164 publications
(196 citation statements)
references
References 37 publications
10
179
2
2
Order By: Relevance
“…In many cases, siRNA accumulation at endogenous genomic loci is not sufficient to induce DNA methylation, as in the epiallele fwa-d in Arabidopsis [54] or the B-I paramutable allele of maize [55]. In other cases, a significantly decreased abundance of siRNAs does not reduce DNA methylation levels [22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In many cases, siRNA accumulation at endogenous genomic loci is not sufficient to induce DNA methylation, as in the epiallele fwa-d in Arabidopsis [54] or the B-I paramutable allele of maize [55]. In other cases, a significantly decreased abundance of siRNAs does not reduce DNA methylation levels [22].…”
Section: Discussionmentioning
confidence: 99%
“…Since the Pol IV-interacting protein DTF1/SHH1 binds to H3K9me2 and helps recruit Pol IV to a subset of RdDM loci [21,22], we tested the possibility that DTF1/ SHH1 preferentially targets ID and/or PD loci. However, we found that the ID loci are less enriched for DTF1-dependent DMRs (Supplementary information, Figure S5), suggesting that multiple factors are involved in recruiting Pol IV to different types of RdDM target loci.…”
Section: Dicer-independent Dna Methylation At Rddm Target Locimentioning
confidence: 99%
See 2 more Smart Citations
“…In RdDM pathways acting at predominantly transposable elements (TEs), SAWADEE HOMEODOMAIN HOMOLOG (SHH)1 binds and recruits RNA Polymerase IV (PolIV) to transcribe methylated DNA (3,4). The PolIV transcripts are then made double-stranded by RNA-dependent RNA polymerase (RDR)2 and cleaved by Dicer-like 3 (DCL3) into 24-nt sRNAs that are loaded into and guide AGONAUTE (AGO)4 to complementary scaffold RNAs transcribed from the same locus by RNA polymerase V (PolV).…”
mentioning
confidence: 99%